1999
DOI: 10.1099/00221287-145-9-2415
|View full text |Cite
|
Sign up to set email alerts
|

A multicopper oxidase gene from Candida albicans: cloning, characterization and disruption b bThe EMBL accession number for the sequence reported in this paper is Y09329.

Abstract: A multicopper oxidase gene from the human pathogenic yeast Candida albicans was isolated and characterized. An open reading frame of 1872 bp, designated CaFET3, was identified, encoding a predicted protein of 624 amino acids and a molecular mass of 70 5 kDa. The identity between the deduced amino acid sequences of CaFET3 and the Saccharomyces cerevisiae FET3 gene is 55 %. CaFET3 was localized on chromosome 6. A null mutant (fet3∆/fet3∆) was constructed by sequential gene disruption. Unlike the C. albicans SC53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 29 publications
1
73
1
Order By: Relevance
“…Deletion of CaFET3 resulted in reduced adhesiveness to fibroblasts, although no significant differences were observed between the virulence of the wild type and the Δ/Δfet3 strain in a mouse model of systemic candidiasis [29]. In contrast with C. albicans , upon the removal of the ortholog of FET3 in C. parapsilosis indeed influenced the fungi’s virulence in vivo, given the lower amount of fungal burden measured.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of CaFET3 resulted in reduced adhesiveness to fibroblasts, although no significant differences were observed between the virulence of the wild type and the Δ/Δfet3 strain in a mouse model of systemic candidiasis [29]. In contrast with C. albicans , upon the removal of the ortholog of FET3 in C. parapsilosis indeed influenced the fungi’s virulence in vivo, given the lower amount of fungal burden measured.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, it has been observed that deletions in genes that facilitate high-affinity copper uptake or delivery of copper ions to the multicopper oxidase ScFet3p result in strains that also display defective high-affinity iron uptake (Knight et al, 1996;Lin et al, 1997;Yuan et al, 1995). Furthermore, growing evidence suggests that reductive iron uptake in C. albicans may also be dependent on copper uptake (Eck et al, 1999;Knight et al, 2002;Weissman et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…A homozygous deletion of CaCCC2 results in strains with defective high-affinity iron uptake, presumably as a result of incorrect delivery and incorporation of copper into CaFet3p (Weissman et al, 2002). However, although reductive iron uptake has been shown to be reliant on copper in C. albicans, Cafet3 and Caccc2-null mutants were still able to set up a systemic infection in mice (Eck et al, 1999). Furthermore, the virulence of a Caarn1-null mutant was also unaffected (Hu et al, 2002).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Two genes, CFL1 (Hammacott et al, 2000) and RBT2 encode functional surface ferrireductases homologous to the S. cerevisiae Fre family. CaFET3, a multicopper oxidase gene involved in high-affinity ferrous transport, was recently cloned (Eck et al, 1999), and the high-affinity iron permease CaFTR1 was shown to be required for C. albicans virulence (Ramanan and Wang, 2000).…”
Section: Introductionmentioning
confidence: 99%